ON THE RELATIVITY OF THE LIMITS OF PUBLIC AND PRIVATE INTERESTS IN CRIMINAL PROCEEDINGS - TARASOV Aleksandr Alekseyevich (Правовое государство: теория и практика)
The distinction between private and public interests and the search for a balance between them in the system of criminal procedure regulation are in one way or another connected with all other theoretical and practical problems of criminal proceedings and criminal procedure policy. The issues of the relationship between public and private interests have always been at the epicentre of scientific discussions and acute ideological confrontation. Purpose: to show that in criminal proceedings, the overriding publicity of which has never been questioned, the protection of the legitimate private interests of participants in criminal proceedings and other persons dependent on those proceedings has always constituted a public interest as well. Methods: the historical method allows us to trace the dynamics of the formation of scientific ideas about the relationship between public and private interests in criminal proceedings; the concrete legal method consists in comparing these ideas with the requirements of the law in force in different historical periods; the method of structural-system analysis and synthesis is used to substantiate the author’s position on the subjects representing each of the analysed interests in specific legal relations, on the content of these interests and their correlation in each case. Results: the article formulates a conclusion about the conditionality of dividing the interests protected in criminal proceedings into public and private ones, since the public beginning of the entire criminal procedure presupposes equal protection of each legitimate interest, no matter who is its bearer in a particular situation. This approach allows ensuring the protection of society and each person from both crimes and abuses of power that pose an equal threat to public interests.